A low-cost, open-source device to evaluate limb stiffness in a rabbit model of cerebral palsy - Steele, Preston R.; Feldmann, Joel; Quinlan, Katharina A.; Manuel, Marin (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundMovement disorders such as cerebral palsy (CP) are frequently associated with joint and muscle stiffness, often evaluated using subjective clinical methods like the Modified Ashworth Scale or Tardieu Scale. These approaches lack precision and reproducibility, particularly in preclinical models, limiting their utility in translational research.MethodsThis study presents the development of a low-cost, open-source torquemeter device tailored for use in a neonatal rabbit model of CP. The device is designed to quantify joint stiffness objectively by measuring torque across a range of controlled joint rotation speeds, a key factor in evaluating hypertonia associated with spasticity and dystonia. The construction process is straightforward, with all components being either commercially available or 3D-printable and requiring only basic assembly tools.ResultsThe torquemeter demonstrated precise, reproducible measurements of torque and joint stiffness in pilot studies, validating its applicability in preclinical settings. By eliminating subjective biases, the device provides robust data to assess the effectiveness of therapeutic interventions targeting spasticity.ConclusionThis low-cost torquemeter offers an accessible, reliable tool for preclinical movement disorder research. Its ability to quantify limb stiffness with high precision enhances the evaluation of treatment strategies in CP models, paving the way for improved therapeutic development and outcomes.